(Re)membering history: performative disinterment in post-TRC South African theatre-making - Chauke, Lesego (Department of Drama, 2020)
With the socio-political and even the theatre landscape in South Africa being fraught with questions of identity, ownership, memory and self-representation, I’m often struck by the implications of representing the self, while noting that the ‘self’ is never and can never be fully removed from some sense of a collective. This dissertation is a proliferation of questions and provocations that I hope will begin to sketch out an emergent body of South African performance work, particularly by young, Black female makers that centres materiality and corporeality as a device through which to resist the particularly logocentric and text-centric dramaturgy of the South African TRC proceedings. This dissertation will unfold as a kind of discourse analysis, drawing from a range of materials in an attempt to arrive at a theory of performative disinterment. While I draw from critical theory and performance studies, the core concepts that I return to throughout the dissertation are language, materiality and dramaturgy. These are defined primarily in relationship to each other, and it is this relationship that forms the basis for performative disinterment. Performative disinterment, as I conceive of it, is a productive suspicion of history that plays itself out through performance. It encourages a dramaturgy of materiality to give language to and articulate memory as counterpoint to history. I employ theatre and performance as an analytical tool through which to deconstruct the South African Truth and Reconciliation Commission looking specifically at the relationship between memory and the representation thereof in the Commission’s proceedings. I turn to Susan Lori Park’s play Venus and Sara Warner’s analysis of the play, focussing on what Warner calls ‘a drama of disinterment’ as a counterpoint to the dramaturgy of the TRC so as to begin to presence a terrain of performance work that employs ‘mis’-representation as a device for theatrical representation-ability. I conclude with an analysis of A Faint Patch of Light (2018), directed by Qondiswa James and They Look at Me and This is All They Think (2006), directed by Nelisiwe Xaba as contemporary South African performances that resists tropes of spectacle and the dominant gaze.